Smart Paper Circuit sebagai Media Edukasi Listrik pada Anak Usia Dini di TK Dayyinah Kids 2 - Nabila Aulia Ramadhani -; Furqon Andika; Fortinov Akbar Irdam (Politeknik Caltex Riau, 2025)
Early childhood is considered a golden period of development, during which educational processes must align with children’s physical, mental, social, and emotional growth stages. One effective learning approach for fostering cognitive development in early childhood is project-based experimental learning that integrates elements of science, technology, engineering, arts, and mathematics (STEAM). This community service activity aimed to introduce the basic concepts of electricity to children at Dayyinah Kids 2 Kindergarten through a hands-on experiment of creating a smart paper circuit. The method employed included demonstration and direct practice with scaffolding, where students were guided in assembling simple electric circuits using LEDs, copper tape, and coin batteries on illustrated paper. The activity involved 40 students from three kindergarten classes and was conducted over a 2.5-hour session. Each student colored their own paper and built the circuit with guidance from a team of facilitators. At the end of the session, assessment was conducted through observation and questionnaires given to both students and teachers. Evaluation results showed that most students demonstrated high enthusiasm, were able to identify basic components, and responded positively to the activity. This program proves that introducing science and technology concepts can be enjoyable and effective at an early age.